2017
DOI: 10.1002/14651858.cd012214.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Metformin for endometrial hyperplasia

Abstract: At present, evidence is insufficient to support or refute the use of metformin alone or in combination with standard therapy - specifically, megestrol acetate - versus megestrol acetate alone, for treatment of endometrial hyperplasia. Robustly designed and adequately powered randomised controlled trials yielding long-term outcome data are needed to address this clinical question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…A 2017 Cochrane systematic review reported on three studies that studied the effects of metformin on endometrial hyperplasia; only one of these studies compared the effects of progestin and metformin with progestin alone. 12 Since then, additional studies have been added to the literature, and have also examined outcomes for patients with atypical hyperplasia and those with endometrial carcinoma. Although atypical endometrial hyperplasia is a pre-cancerous disease state, there is significant overlap between patients with atypical hyperplasia and those found to have invasive carcinoma after hysterectomy.…”
Section: Highlightsmentioning
confidence: 99%
“…A 2017 Cochrane systematic review reported on three studies that studied the effects of metformin on endometrial hyperplasia; only one of these studies compared the effects of progestin and metformin with progestin alone. 12 Since then, additional studies have been added to the literature, and have also examined outcomes for patients with atypical hyperplasia and those with endometrial carcinoma. Although atypical endometrial hyperplasia is a pre-cancerous disease state, there is significant overlap between patients with atypical hyperplasia and those found to have invasive carcinoma after hysterectomy.…”
Section: Highlightsmentioning
confidence: 99%
“…Endometrial hyperplasia is an abnormal thickening of endometrium due to excess estrogen exposure or low progesterone which counteracts the enhancing action of estrogen on growth. Due to the associated hormonal changes, it is most common in females who are postmenopausal or have reached the reproductive age (Clement et al 2017). It may also happen secondary to diabetes, overweight, hypertension, or polycystic ovary.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the endometrial glands of PCOS rats appeared to overgrowth even hyperplasia, not only the gland number increased but also the gland size enlarged. And when the rats underwent EX or MET treatment, the gland number decreased and the gland size narrowed, which inferred that either EX or MET could improve the endometrial hyperplasia that is a common pathological state in PCOS, and MET may have therapeutic bene ts for PCOS patients in endometrial hyperplasia, and some studies have already prompted or con rmed [12,13]. We have investigated that EX or MET in uenced the ovaries of PCOS rats, not only in the ovarian morphology but also in the ovarian reservation function [8,9], and similarly, in the endometrium of PCOS mice models, we also found EX or MET were able to y positive effect on endometrial glands in PCOS rats.…”
Section: Discussionmentioning
confidence: 99%